Dynamic Effects Of Interaction Between Economic Growth, Investment And Savings With International Trade In Indonesia - Tajul Ula (IAIN Langsa, 2023)
Anticipation of economic uncertainty needs to be done to avoid the brink of crisis by maintaining the pace of economic growth, investment and savings climate as well as smooth international trade. This study aims to analyze and explore the dynamic relationship interaction between economic growth variables projected as Gross Domestic Product (GDP), investment, gross domestic savings and international trade of the Indonesian state with data in the period 1971-2020 obtained from the worldbank.org website. The research method uses the Vector Auto Regression (VAR) analysis model with the development of Impulse Response Function (IRF) and Variance Decomposition (VDC) analysis to explain the response of a variable to the shock of the variable itself and other variables. The results of the analysis revealed that the one-way relationship for the variables of investing, saving, and trading was influenced by the variable itself with a lag of one. In addition, the results of IRF analysis show that the variable response of economic growth, investment, savings and international trade is dominated by shocks to economic growth variables, and the results of VDC analysis show that economic growth variables most contribute to the variable response of economic growth itself, investment, savings and international trade. The results of this study can be used as a reference for the formulation of anticipatory policies by the government and Bank Indonesia in preventing the risk of economic crisis by maintaining macroeconomic variable stability so that the level of domestic market confidence is maintained in the outlook. Therefore, the policy stages that can be carried out are to control inflation, reduce the current account deficit, maintain fiscal balance and improve in managing foreign debt.